Tecnologias digitais e a prática docente nos cursos de licenciatura em história e matemática - Paini, Tarciane Dresch (My University, 2019)
The present research aims to investigate how digital technologies are being articulated the teaching practice in the training of students in undergraduate courses in history and mathematics of a university in the countryside of the state Rio Grande do Sul. The theoretical framework has its base on the concepts of digital technologies, digital culture, cyberculture, cyberspace, teacher training, education degree and teaching practice in higher education. Among the most important authors are Vani Moreira Kenski, Pierre Lévy, André Lemos, Maurice Tardif, Maria Cândida Moraes, Manuel Castells and Paulo Freire. The corpus of the research constitutes from the realization of a focus group carried out with the students of the internship subjects and with the students of the Programa Institucional de Iniciação à Docência (PIBID) of the undergraduate courses in history and mathematics. The datas were analyzed using the discursive textual analysis method according to Moraes and Galiazzi (2011). From the analysis we present the following emerging categories: use of technology as a resource; use of technology for the education degree students to learn the content to don’t apply to their teaching practice; difficulty in transposing what has been learned to the teaching activity; detachment from traditional forms of teaching; infrastructure difficulties to use technologies in the classroom; poor qualification of teachers to use technologies; change of paradigm to use digital technologies and offer of pedagogical disciplines in undergraduate degrees. After articulating these categories based on the theoretical framework, it was possible to identify that digital technologies are being articulated the teacher training in undergraduate courses in history and mathematics as a method of learning, where the teacher uses digital technologies, so that his student learns the content of discipline. Through the reports, it is possible to say that there were indications of the teachers to make students look for the knowledge and the exploitation of these resources, being the responsibility of these students the reflection on these practices in order to try to transpose them to their teaching action. The results indicate that we are in a moment of transition, in which pedagogical practices contemplate the use of technologies as a resource with the potential to teach and learn its programmatic content, and it is up to the education degree student to reflect and transpose this form of teaching to his/her teaching activity. These practices are related to tips and 12 suggestion sites, educational software among other resources, encouraging the education degree student to search deeply these forms of teaching. Even though there are no specific subjects related to teaching through digital technologies, the course offers important experiences when the teacher in training is aware of his/her role and has the ability to reflect on the numerous practices experienced in the education degree course for his teaching practice.
A presente pesquisa tem por objetivo investigar como as tecnologias digitais estão sendo articuladas a prática docente na formação dos alunos nos cursos de licenciatura em História e Matemática de uma universidade do interior do estado do Rio Grande do Sul. O quadro teórico teve como base os conceitos de tecnologias digitais, cultura digital, cybercultura, cyberespaço, formação docente, licenciaturas e prática docente no ensino superior. Entre os autores mais importantes podemos destacar Vani Moreira Kenski, Pierre Lévy, André Lemos, Maurice Tardif, Maria Cândida Moraes, Manuel Castells e Paulo Freire. O corpus da pesquisa foi constituído a partir da realização de um grupo focal realizado junto aos alunos das disciplinas de estágio e com os alunos do Programa Institucional de Iniciação à Docência (PIBID) dos cursos de licenciatura em História e Matemática. Os dados foram analisados mediante o método de análise textual discursiva segundo Moraes e Galiazzi (2011). Da análise apresentamos as seguintes categorias emergentes: uso da tecnologia como recurso; utilização da tecnologia para o licenciando aprender o conteúdo não para aplicar a sua prática docente; dificuldade de transpor o que se aprendeu para a ação docente; desapego das formas tradicionais de ensino; dificuldades de infraestrutura para a utilização das tecnologias em sala de aula; deficiente qualificação dos professores para o uso das tecnologias; mudança de paradigma para a utilização das tecnologias digitais e oferta de disciplinas pedagógicas nas licenciaturas. Após a articulação dessas categorias com base no quadro teórico, foi possível identificar que as tecnologias digitais estão sendo articuladas à formação docente nos cursos de licenciatura em História e Matemática como método de aprendizagem, em que o professor universitário se utiliza das tecnologias digitais para que o seu aluno aprenda o conteúdo da disciplina. Através dos relatos é possível dizer que houve indicações dos professores para que os alunos fossem em busca do conhecimento e da exploração desses recursos, cabendo a esses alunos a reflexão sobre essas práticas de forma a tentar transpô-las para a sua ação docente. Os resultados indicam que estamos num momento de transição, em que as práticas pedagógicas contemplam o uso das tecnologias como um recurso com potencial para ensinar e aprender o seu conteúdo programático, cabendo ao licenciando refletir e transpor essa forma de ensino para a sua ação 10 docente. Essas práticas estão relacionadas a dicas e sugestão sites, softwares educativos entre outros recursos, incentivando o licenciando a ir em busca do aprofundamento dessas formas de ensino. Mesmo não havendo, na licenciatura, disciplinas específicas relacionadas ao ensino através das tecnologias digitais, o curso oferece experiências importantes quando o professor em formação está consciente do seu papel e tem a capacidade de refletir sobre as inúmeras práticas experenciadas na licenciatura para a sua prática docente.
Keywords: Inovações educacionais; Professores - Formação; Ensino auxiliado por computador; Aprendizagem educacional; Ensino superior; Educational innovations; Teachers, Training of; Computer-assisted instruction; Educational learning; Higher education